Perceived Discrimination, Patient Trust, and Adherence to Medical Recommendations Among Persons with Sickle Cell Disease - Haywood, Carlton (J Gen Intern Med, 2014)
BACKGROUND: Adults with sickle cell disease (SCD) report experiencing discriminatory behavior from some healthcare providers. The impact of discrimination on health outcomes in SCD, including adherence to physician recommendations, is not known. OBJECTIVE: Our aim was to evaluate the association between perceived discrimination from healthcare providers and nonadherence to physician recommendations among persons with SCD, and to test the potentially mediating role of patient trust. PARTICIPANTS: Patients with SCD (age 15 years and older) participating in the Improving Patient Outcomes with Respect and Trust (IMPORT) Study. MAIN MEASURES: Perceived discrimination from healthcare providers and reported adherence to physician recommendations were assessed by patient self-report using items from the 2001 Commonwealth Fund Health Survey. Interpersonal trust in medical professionals was assessed using the short form of the Wake Forest Trust in Medical Professionals instrument. DESIGN: We used a cross-sectional analysis of IMPORT participant data. Multivariable Poisson regression models were used to test the independent association of discrimination with adherence and to test patient trust as a potential mediator. KEY RESULTS: Among 273 SCD patients with complete data on all variables of interest, patients reporting experiences of discrimination in the healthcare system were 53 % more likely to also report being nonadherent to physician recommendations. Trust in medical professionals appeared to mediate the discrimination/nonadherence relationship, accounting for 50 % of the excess prevalence of nonadherence among those experiencing discrimination. CONCLUSION: SCD patient perceptions of discriminatory experiences from healthcare providers are associated with greater nonadherence to physician recommendations, and may be a potential factor contributing to disparities in health and health quality among this patient population. Perceived discrimination appears to affect adherence behaviors through the pathway of patient trust. Improving relationships between healthcare providers and SCD patients may improve the trust that SCD patients have in medical professionals, which in turn may improve other outcomes among this underserved patient population.